Subalternitas Perempuan dalam Cerpen “Inem” dan “Pelarian Yang Tak Dicari” karya Pramoedya Ananta Toer: The Woman Subalternity in “Inem” Short Story and “Pelarian Yang Tak Dicari” Short Story Written by Pramoedya Ananta Toer - Siti Hardiyanti Amri (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2020)
This research studies about women subaltern in the two short stories of Pramoedya Ananta Toer. Through his works, Pramoedya potrays gender inequality in which women are positioned marginally. Both characters do not have ability to voice themselves which Spivak mentions as subaltern. The research problems are the structure of the two short stories and the position of subaltern in the structure. This research uses deconstruction analysis method. The results indicate that there is such resistance by those oppressed group. Meanwhile, the author presents not only the subaltern who acts passively throughout the text, but also makes effort to fight for freedom. However, the voice of them are not heard. They remain under the oppression of men.